Validation of an Association Rule Mining-Based Method to Infer Associations Between Medications and Problems - Wright, A.; McCoy, A.; Henkin, S.; Flaherty, M.; Sittig, D. (Applied Clinical Informatics, 2013)
Background: In a prior study, we developed methods for automatically identifying associations between medications and problems using association rule mining on a large clinical data warehouse and validated these methods at a single site which used a self-developed electronic health record. Objective: To demonstrate the generalizability of these methods by validating them at an external site.Methods: We received data on medications and problems for 263,597 patients from the University of Texas Health Science Center at Houston Faculty Practice, an ambulatory practice that uses the Allscripts Enterprise commercial electronic health record product. We then conducted association rule mining to identify associated pairs of medications and problems and characterized these associations with five measures of interestingness: support, confidence, chi-square, interest and conviction and compared the top-ranked pairs to a gold standard.Results: 25,088 medication-problem pairs were identified that exceeded our confidence and support thresholds. An analysis of the top 500 pairs according to each measure of interestingness showed a high degree of accuracy for highly-ranked pairs.Conclusion: The same technique was successfully employed at the University of Texas and accuracy was comparable to our previous results. Top associations included many medications that are highly specific for a particular problem as well as a large number of common, accurate medication-problem pairs that reflect practice patterns.Citation: Wright A, McCoy A, Henkin S, Flaherty M, Sittig D. Validation of an association rule mining-based method to infer associations between medications and problems. ppl Clin Inf 2013; 4: 100–109http://dx.doi.org/10.4338/ACI-2012-12-RA-0051
Keywords: Problem list; clinical decision support; data mining; automated inference; methodology